PELATIHAN LITERASI KEUANGAN SYARIAH DALAM MENGHADAPI PANDEMI COVID 19 UNTUK PARA DAI DI BEKASI - Anam, Moh. Khoirul; Choirin, Moh (Center of Community Service (PPM), Institute for Research and Community Services (LP2M) UI, 2022)
With the predicate as a developing country, Indonesia has a tendency to lower economic growth than countries in the Southeast Asian region. This is due to several aspects, including the lack of understanding of the Indonesian people on financial literacy. Dai circles are identical community groups that have small incomes but have good Islamic knowledge. Dai has the potential to manage finances well. This service aims to provide financial training to preachers in Bekasi. By providing this training, it is hoped that the preachers will understand financial recording and management, how to access banking services, and how to use savings products and financing products. The service activity went well with an estimated 50 participants and the discussion was running enthusiastically. Participants experienced an increase in financial literacy knowledge.Dengan predikat sebagai Negara berkembang, Indonesia memiliki pertumbuhan ekonomi cenderung lebih rendah dari pada negara negara di wilayah Asia Tenggara. Hal ini disebabkan oleh beberapa aspek, diantaranya adalah minimnya pemahaman masyarakat Indonesia terhadap literasi keuangan. Kalangan Dai merupakan kelompok masyarakat identik memiliki pendapatan kecil tetapi menguasai keilmuan keIslaman yang baik. Dai berpotensi untuk mengelola keuangan yang baik. Pengabdian ini bertujuan untuk memberikan pelatihan keuangan kepada para dai di Bekasi. Dengan memberikan pelatihan ini diharapkan para dai memahami pencatatan dan pengelolaan keuangan, bagaimana mengakses layanan perbankan, bagaimana menggunakan produk tabungan dan produk